Understanding Parental Guilt in Caregivers of Children with Behavioral Disorders - Lee, Angel; Yildiz, Emre; Chaudhary, Aman Ullah (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: This study aims to explore the experiences of parental guilt in caregivers of children with behavioral disorders in Turkey, focusing on emotional, social, and coping dimensions. Methods and Materials: A qualitative research design was employed, using semi-structured interviews to collect data from 27 caregivers of children with behavioral disorders. Participants were selected through purposive sampling, ensuring diversity in age, gender, and child diagnosis. Data were analyzed using thematic analysis, and NVivo software was used to organize and identify emergent themes. The study utilized theoretical saturation, with interviews conducted until no new themes emerged. Findings: Three main themes emerged from the data: Emotional Burden, Social Pressure and Stigma, and Coping and Adaptation. Caregivers reported persistent self-blame, emotional exhaustion, and feelings of inadequacy, often linked to internalized shame and societal expectations. Social pressure, particularly from extended family and educational institutions, exacerbated guilt. Coping strategies included seeking professional help, peer support, spiritual practices, and cognitive reframing, which helped mitigate guilt but were often insufficient without systemic support. Conclusion: Parental guilt in caregivers of children with behavioral disorders is a complex emotional experience shaped by personal beliefs, societal judgments, and the demands of caregiving. The study highlights the need for targeted interventions and support systems that address caregivers’ emotional burden, including counseling, peer support groups, and education on child development. Understanding the cultural context is crucial in designing effective interventions that can alleviate caregiver guilt and improve well-being.